Increased expression of H19/miR‐675 is associated with a low fat‐free mass index in patients with COPD. Issue 3 (5th January 2016) - Lewis, Amy; Lee, Jen Y.; Donaldson, Anna V.; Natanek, S. Amanda; Vaidyanathan, Srividya; Man, William D.‐C.; Hopkinson, Nicholas S.; Sayer, Avan A.; Patel, Harnish P.; Cooper, Cyrus; Syddall, Holly; Polkey, Michael I.; et al.
Abstract: Background: Loss of muscle mass and strength is a significant comorbidity in patients with chronic obstructive pulmonary disease (COPD) that limits their quality of life and has prognostic implications but does not affect everyone equally. To identify mechanisms that may contribute to the susceptibility to a low muscle mass, we investigated microRNA (miRNA) expression, methylation status, and regeneration in quadriceps muscle from COPD patients and the effect of miRNAs on myoblast proliferation in vitro . The relationships of miRNA expression with muscle mass and strength was also determined in a group of healthy older men. Methods: We identified miRNAs associated with a low fat‐free mass (FFM) phenotype in a small group of patients with COPD using a PCR screen of 750 miRNAs. The expression of two differentially expressed miRNAs (miR‐675 and miR‐519a) was determined in an expanded group of COPD patients and their associations with FFM and strength identified. The association of these miRNAs with FFM and strength was also explored in a group of healthy community‐dwelling older men. As the expression of the miRNAs associated with FFM could be regulated by methylation, the relative methylation of the H19 ICR was determined. Furthermore, the proportion of myofibres with centralized nuclei, as a marker of muscle regeneration, in the muscle of COPD patients was identified by immunofluorescence. Results: Imprinted miRNAs (miR‐675 and from a cluster, C19MC which includes miR‐519a) were differentially expressed in the quadriceps of patients with a low fat‐free mass index (FFMI) compared to those with a normal FFMI. In larger cohorts, miR‐675 and its host gene (H19) were higher in patients with a low FFMI and strength. The association of miR‐519a expression with FFMI was present in male patients with severe COPD. Similar associations of miR expression with lean mass and strength were not observed in healthy community dwelling older men participating in the Hertfordshire Sarcopenia Study. Relative methylation of the H19 ICR was reduced in COPD patients with muscle weakness but was not associated with FFM. In vitro, miR‐675 inhibited myoblast proliferation and patients with a low FFMI had fewer centralized nuclei suggesting miR‐675 represses regeneration. Conclusions: The data suggest that increased expression of miR‐675/H19 and altered methylation of the H19 imprinting control region are associated with a low FFMI in patients with COPD but not in healthy community dwelling older men suggesting that epigenetic control of this loci may contribute to a susceptibility to a low FFMI.